The Effectiveness of Project Based Learning and Discovery Learning with Modul to Improve Learning Outcome for AutoCAD Subject - Ashfahani, Aufa; Haryono, Haryono; Kustiono, Kustiono (Innovative Journal of Curriculum and Educational Technology, 2020)
In fact of AutoCAD learning, there is still the use of conventional method. So, the students does not achieve the quality maximally. It is important to make the innovation of learning model in order to produce the competent outcomes. This study aims to determine the effectiveness of Project Based Learning and Discovery Learning with module to increase learning outcome of AutoCAD subject. Those are three main parts of this study. The first is the different influence between Project Based Learning and Discovery Learning on the learning outcome, the second is the different influence between male and female on the learning outcomes and the third is the interaction between Project Based Learning, Discovery Learning and gender on the learning outcome. This research was 2x2 factorial experiment with a quantitative approach. The data source of this study were 186 students of class XI of SMKN (Vocational School) 4 Semarang in the 2019/2020 school year. From 186 students, there were 36 students of class XI TGB1 as the experimental class and 37 students of class XI TGB2 as the control class. The results shows that Project Based Learning model and Discovery Learning with module could improve students’ learning outcomes in SMK 4 grade XI. From the gender interaction aspect of the Project Based Learning model and Discovery Learning, it shows the learning outcomes for male are higher than female. Thus, the Project Based Learning model is appropriate for AutoCAD subject because it can prepare students to face the workforce.